2018
DOI: 10.1002/nop2.168
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cut‐off scores for interpretation of the Heart Failure Impact Questionnaire

Abstract: AimsHeart failure (HF) influences health‐related quality of life. However, the factors that contribute to health‐related quality of life remain unclear in Taiwan. We aim to identify the factors influencing health‐related quality of life in HF patients.MethodsHospitalized HF (N = 225) patients were included from April 2011 to April 2014. Health‐related quality of life was assessed by using the 36‐Item Short‐Form Health Survey (SF‐36) and the Minnesota Living with Heart Failure Questionnaire. A new cut‐off was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
3
7
0
1
Order By: Relevance
“…Older age was signi cantly associated with poor HRQoL. This nding is consistent with the study done in Taiwan (22). A cross-sectional study from Saudi Arabia and a systematic review from Iran also reported a signi cant relationship between age and health-related quality of life (30,31).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Older age was signi cantly associated with poor HRQoL. This nding is consistent with the study done in Taiwan (22). A cross-sectional study from Saudi Arabia and a systematic review from Iran also reported a signi cant relationship between age and health-related quality of life (30,31).…”
Section: Discussionsupporting
confidence: 87%
“…But this nding is lower than a study done in Taiwan. This may be due to study participant differences as in Taiwan study participants were NYHA class-to NYHA class-and had the previous hospitalization for at least two times (22).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(1) Not only does it affect the health and wellbeing of the subject but also adversely impacts families and communities, also increasing disability, burden of disease, hospital admissions, and expenditure, causing a considerable strain on a society with scarce resources. (2,3) There is an increasing trend in the incidence and prevalence of HF (1,4) with increasing life span (21). Poor health related quality of life due to HF is one of the factors for high rates of recurrent prolonged hospitalization and markedly increased burden on hospital services due to this condition.…”
Section: Introductionmentioning
confidence: 99%